Answer:
C. ![3j^{3}l](https://tex.z-dn.net/?f=3j%5E%7B3%7Dl)
Step-by-step explanation:
1) First you cancel
because they are completely the same. then you take out the constants and simply.
2)You then have to use the Quotient Rule:
![\frac{x^{a} }{x^{b} } =x^{a - b}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7Ba%7D%20%7D%7Bx%5E%7Bb%7D%20%7D%20%3Dx%5E%7Ba%20-%20b%7D)
You should have ...
![3j^{6-3} l^{5-4}](https://tex.z-dn.net/?f=3j%5E%7B6-3%7D%20l%5E%7B5-4%7D)
3) Simplify 6 − 3 to 3.
![3j^{3} l^{1}](https://tex.z-dn.net/?f=3j%5E%7B3%7D%20l%5E%7B1%7D)
4) Simplify 5 − 4 to 1.
5) Use Rule of One: ![x^{1} =x](https://tex.z-dn.net/?f=x%5E%7B1%7D%20%3Dx)
Answer is !!!
![3j^{3} l](https://tex.z-dn.net/?f=3j%5E%7B3%7D%20l)
To answer this question, apply this formula <span>P(m and a) = P(m) + P(a) - P(m or a). Where m stands for marinara and a stands for alfredo.
</span><span>P(m and a) = P(m) + P(a) - P(m or a)
</span><span>P(m and a) = 0.64 + 0.56 - 0.89
</span><span>P(m and a) = 0.31</span>
Answer: 0=0 The input is an identity or it is true for all values
-3(2x+6)=-6x-18
(-3*2x)+(-3*6)=-6x-18
-6x+-18=-6x-18
0=0
Answer:
first one
Step-by-step explanation:
the sum of (9k-4) =3542
so it will be the first one because
28((5+248)/2)=3542